2019
DOI: 10.1111/ajo.13002
|View full text |Cite
|
Sign up to set email alerts
|

Birth outcomes in Aboriginal mother–infant pairs from the Northern Territory, Australia, who received 23‐valent polysaccharide pneumococcal vaccination during pregnancy, 2006–2011: The PneuMum randomised controlled trial

Abstract: Background Pregnant women and infants <6 months old have a high baseline risk for pneumococcal disease compared to the general population, particularly among Indigenous populations living in poverty and low‐resource settings. Efficacy trials of pneumococcal vaccination in pregnancy examining adverse birth outcomes are lacking. Aims We report adverse birth events as secondary outcomes from the ‘PneuMum’ randomised controlled trial of 23‐valent pneumococcal polysaccharide vaccination (23vPPV) in pregnancy (Augus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The majority of vaccines did not contain any adjuvants, although some incorporated adjuvants including aluminium hydroxide or phosphate. The characteristics of the nine included studies are described in table 1 25–33…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of vaccines did not contain any adjuvants, although some incorporated adjuvants including aluminium hydroxide or phosphate. The characteristics of the nine included studies are described in table 1 25–33…”
Section: Resultsmentioning
confidence: 99%
“…When assessing the RoB, four articles were identified as low RoB,25–27 33 one article with some concerns29 and four articles as high RoB 28 30–32. A detailed assessment of the RoB is available in online supplemental table S3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AMSTAR 2 Risk of Bias for Systematic Review tool [ 14 ] was applied by the authors to the review process. In this context, two questions in the tool were deemed to be not applicable due to their focus on evidence synthesis or meta-analysis, as the systematic review focus was on quality of design and implementation.…”
Section: Methodsmentioning
confidence: 99%
“…Several other NT studies have also investigated speci c factors and their impact on birth outcomes, including gestational age at birth. Such studies have examined the impact of sexually transmitted infections [7], vaccinations during pregnancy, [8,9]and young maternal age [10], none of which were signi cantly associated with PTB risk. One study showed a higher rate of PTB in those with (versus without) rheumatic heart disease, [11] whereas two studies found lower rates of PTB in those receiving enhanced models of pregnancy care [12,13].…”
mentioning
confidence: 99%